2018
DOI: 10.1002/anie.201711328
|View full text |Cite
|
Sign up to set email alerts
|

An Aluminum–Sulfur Battery with a Fast Kinetic Response

Abstract: The electrochemical performance of the aluminum-sulfur (Al-S) battery has very poor reversibility and a low charge/discharge current density owing to slow kinetic processes determined by an inevitable dissociation reaction from Al Cl to free Al . Al Cl Br was used instead of Al Cl as the dissociation reaction reagent. A 15-fold faster reaction rate of Al Cl Br dissociation than that of Al Cl was confirmed by density function theory calculations and the Arrhenius equation. This accelerated dissociation reaction… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
138
0
3

Year Published

2018
2018
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 173 publications
(143 citation statements)
references
References 21 publications
2
138
0
3
Order By: Relevance
“…The problem in this study by Gao et al. was the large voltage hysteresis, which was ascribed to the slow kinetic processes of the dissociation reaction from Al 2 Cl 7 − to free Al 3+ during discharge, as proposed by Li and co‐workers . Li and co‐workers further revealed that a fast kinetic response could be achieved by using Al 2 Cl 6 Br − instead of Al 2 Cl 7 − in the Al‐S battery.…”
Section: Alcl3‐based Electrolytes For Aluminum Batteriesmentioning
confidence: 78%
See 1 more Smart Citation
“…The problem in this study by Gao et al. was the large voltage hysteresis, which was ascribed to the slow kinetic processes of the dissociation reaction from Al 2 Cl 7 − to free Al 3+ during discharge, as proposed by Li and co‐workers . Li and co‐workers further revealed that a fast kinetic response could be achieved by using Al 2 Cl 6 Br − instead of Al 2 Cl 7 − in the Al‐S battery.…”
Section: Alcl3‐based Electrolytes For Aluminum Batteriesmentioning
confidence: 78%
“…In addition to the corrosion of metallic materials, the commonly used PVDF binder has also been found to corrode in the acidic chloride‐based ionic‐liquid electrolyte . The PTFE binder was stable in this electrolyte and was, therefore, used in many studies . An increase in the fraction of AlCl 3 will aggravate corrosion in RABs.…”
Section: Alcl3‐based Electrolytes For Aluminum Batteriesmentioning
confidence: 99%
“…Zusätzlich zu der Korrosion von metallischen Materialien wurde ebenso festgestellt, dass der gängig verwendete PVDF‐Binder auch in dem sauren Chlorid‐ionischen Flüssigelektrolyten korrodiert . Der PTFE‐Binder war in diesem Elektrolyten stabil genug und wurde daher in vielen Studien eingesetzt . Bei steigendem Anteil an AlCl 3 wird sich die Korrosion in RABs verschlimmern.…”
Section: Alcl3‐basierte Elektrolyte Für Aluminiumbatterienunclassified
“…war laut Li et al. die große Spannungshysterese, die den langsamen kinetischen Prozessen der Abscheidungsreaktion von Al 2 Cl 7 − zur Freistellung von Al 3+ während der Entladung zuzuschreiben war . Li et al.…”
Section: Alcl3‐basierte Elektrolyte Für Aluminiumbatterienunclassified
“…[92][93][94] Although the performance of AlÀ S batteries have obtained considerable improvements, detailed mechanism investigation, cathode optimization, and IL electrolyte exploration, in particular, are still demanded to overcome the low rate-capacity and inferior cycling stability of the AlÀ S batteries at this infant stage. However, the AlÀ S battery still suffers from the poor reversibility and slow reaction kinetics.…”
Section: Non-aqueous Aluminum-sulfur/air Batteriesmentioning
confidence: 99%